1995
DOI: 10.1111/j.0022-3646.1995.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF BROMIDE AND IODIDE ON STALK SECRETION IN THE BIOFOULING DIATOM ACHNANTHES LONGIPES (BACILLARIOPHYCEAE)1

Abstract: Extracellular polymeric substance (EPS) secretion was examined in the stalked marine diatom Achnanthes longipes Ag. in defined medium. This common biofouling diatom exhibited an absolute requirement for bromide for stalk production and substratum attachment, whereas elevated iodide concentrations in the growth medium inhibited stalk formation and adhesion. Varying EPS morphologtes resulted from altering bromide and iodide levels: pads, stalk‐pads, stalks, and no EPS. Cells showed no differences in growth with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 60 publications
(51 reference statements)
1
23
0
Order By: Relevance
“…In marine macroalgae, the enzyme vanadiumbromoperoxidase is essential for production of bromoform that plays an important role in eliminating epiphytic microalgae (Ohsawa et al 2001). In species of biofouling diatoms, an absolute requirement of the same enzyme for substratum attachment has been reported (Johnson et al 1995). An elevated concentration of vanadium has also been demonstrated to have an inhibitory effect on the photosynthesis of phytoplankton (Nalewajko et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In marine macroalgae, the enzyme vanadiumbromoperoxidase is essential for production of bromoform that plays an important role in eliminating epiphytic microalgae (Ohsawa et al 2001). In species of biofouling diatoms, an absolute requirement of the same enzyme for substratum attachment has been reported (Johnson et al 1995). An elevated concentration of vanadium has also been demonstrated to have an inhibitory effect on the photosynthesis of phytoplankton (Nalewajko et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological requirement for bromine is poorly documented in diatoms, with most reports confined to the red and brown algae (Fries 1966;McLachlan and Craigie 1967;Wolk 1968). However, Johnson et al (1995) recently demonstrated a nutritional requirement of bromine in the stalked marine diatom Achnanthes. Extracellular polymeric substance (EPS) secretion in this species apparently exhibits an absolute requirement for bromide as both stalk formation and adhesion require this compound.…”
Section: Discussionmentioning
confidence: 99%
“…That A. Zongipes polymers are organized and assembled into networks by phenolic cross-linking components is suggested by several results: (a) the blue autofluorescence of the stalks when excited by UV light >360 nm; (b) Johnson et al (1995) have characterized a bromide dependence for stalk synthesis in A. longipes and also found that iodide inhibits stalk production; and (c) V. Vreeland (personal communication) found preliminary cytochemical evidence for peroxidase activity within intracellular vesicles in A. longipes cells. Phenolic compounds such as dityrosine, ferulic acid, feruloyl esters, caffeic acid, and sinapic acid are known to fluoresce blue when exposed to 366-nm UV light (Fry, 1995).…”
Section: A Longipesmentioning
confidence: 98%